Chronic hepatitis E: a review of the literature. Issue 2 (12th August 2013) - Fujiwara, S.; Yokokawa, Y.; Morino, K.; Hayasaka, K.; Kawabata, M.; Shimizu, T.
Summary In 1978, the first case of hepatitis E was identified as non‐A, non‐B hepatitis. Hepatitis E virus (HEV) infection is believed to be one of the common causes of enterically transmitted acute hepatitis in developing countries and is rare in developed countries, except in patients with a history of travel. However, an increasing number of chronic HEV infection cases have recently been reported in developed countries. In these countries, immunosuppressed patients with HEV infection, such as organ transplant recipients, human immunodeficiency virus (HIV)‐infected patients or patients with haematological malignancies, could develop chronic hepatitis E (CHE) infection. Approximately 60% of HEV infections in immunocompromised patients after solid organ transplantation evolve to CHE without antiviral treatment. Clinical manifestations of CHE are often nonspecific symptoms. Many patients with CHE infection are asymptomatic, but some have jaundice, fatigue, abdominal pain, fever and asthenia. Several extrahepatic manifestations have also been reported. Although chronic HEV infection can result in progressive severe liver failure and cirrhosis, diagnosis is often controversial because of the lack of specific diagnostic criteria. Many CHE cases are diagnosed by HEV RNA‐positive serum or stool for >6 months. Immunosuppressive drugs, interferon‐alpha and ribavirin have been used for treatment. Diagnostic reverse‐transcription polymerase chain reaction is useful for estimating treatment efficacy. Preventive measures for HEV infection have been discussed, while systematic guidelines have not yet been reported.